Protocatechuic acid attenuates intestinal inflammation through TLR4/p38 and NF-κB pathways in heat-stressed broilers - Shuaiyong Wang; Xin Wang; Yu Gao; Yuchen Fu; Zhaoqing Han; Ping Xu; Jianli Tang (Poultry Science)
Protocatechuic acid (PCA), a major active component found in Eucommia ulmoides Oliver, is involved in regulating oxidative stress and inflammation. Heat stress poses a significant threat to the poultry industry. In this study, we investigated the protective effect of PCA on intestinal homeostasis under heat stress. Our results indicated that PCA improved the growth performance of broilers during heat stress. Furthermore, PCA mitigated jejunal damage and attenuated the upregulation of inflammatory mediators, including TNF-α, IL-6, and IL-1β, triggered by heat stress. Concurrently, it restored the activity of superoxide dismutase (SOD) and total antioxidant capacity (T-AOC). Furthermore, PCA maintained the jejunum function by increasing the levels of ZO-1, Claudin-1, and Occludin. Mechanistically, PCA inhibited the activation of TLR4/p38 MAPK and NF-κB pathways, thereby regulating the imbalance in oxidative stress and inflammatory responses caused by heat stress.